Psychosocial impact of caring for children with cerebral palsy on the family in a developing country - Ogwumike, Omoyemi O.; Adeniyi, Fatai A.; Obidiegwu, Chioma J. (Journal of Pediatric Neurology, 2012)
Having a child with cerebral palsy (CP) in developing countries of the world is particularly burdensome. This study investigated psychosocial impact on the family caring for a child with CP, examined possible association of severity of gross motor function impairment on the psychosocial impact and compared impact scores of families with CP child with that of families with no CP child. Participants consisted of 117 parents/caregivers of children with CP and 117 parents/caregivers of children without CP whose children attended purposively selected secondary and tertiary health institutions in South-West region of Nigeria. Impact on family (IOF) scale was used to assess psychosocial impact while gross motor function classification system for CP was used to rate severity of motor function impairment in children with CP. Participants were mostly of low income 59 (25.2%) and middle income 85 (36.3%) categories. Children were mostly in the 1–3 year age range 116 (49.6%). Birth asphyxia was most reported cause of CP and no social support service was reported. Significantly higher mean subscale and total IOF scores were observed in families with CP child (37.4 ± 8.91) compared with families with no CP child (20.8 ± 4.98) P = 0.000. Significant differences did not exist in mean total IOF scores and severity of motor function impairment in children with CP (P = 0.16). Presence of a child with CP imposes tremendous psychosocial challenges on the family irrespective of severity of motor function impairment. Implementation of an effective and accessible social support system by Nigerian policy makers is imperative.
Keywords: Cerebral palsy; psychosocial impact; family; children